A Novel Antimicrobial Stewardship Program-Guided Procalcitonin Initiative for Emergency Department Diagnosis of Bacterial Pneumonia in New York City. (4th October 2017) - Rodriguez, George D; Yashayev, Roman; Yushuvayev, Bella; Kula, Anna; Warren, Nathan; Dhillon, Geeti; Tsapepas, Demetra; Keane, Caroline; Rodgers, William H; Siegal, Jonathan; Sharma, Manish; Segal-Maurer, Sorana
Abstract: Background: An accurate diagnosis of bacterial pneumonia in the Emergency Department (ED) is challenging, resulting in inappropriate antibiotic use, adversely impacting patient care and safety. Procalcitonin (PCT), a serum biomarker, has good positive predictive value for bacterial lower respiratory tract infections. We sought to evaluate the impact of using PCT in an antimicrobial stewardship program (ASP)-driven algorithm to manage patients with presumed pneumonia in the ED. Methods: We performed an IRB-approved quality initiative, 4-month retrospective evaluation of adult patients evaluated for pneumonia using PCT in a 515-bed university-affiliated hospital. Initial PCT use was restricted to ED for hemodynamically stable patients with presumed pneumonia. Subsequent PCT levels were ordered by ASP team members at 8- to 12-hours and days 3, 5, and 7 to guide the duration of antibiotic use and interpreted as per existing guidelines. Prior to start of initiative, aggressive education was provided by ASP to ED staff, followed by algorithm implementation. Outcomes included hospital admission, days of antibiotics, antibiotic use ≤48 hours, total PCT levels, length of stay, and 30-day pneumonia readmission. Results: Baseline demographics of initial 182 patients differed between negative and positive PCT groups with age (78 vs. 84, P = 0.037) and sexfemale (88 vs. 15, P = 0.001). Negative PCT was associated with lower temperature ( P = 0.0002), and white blood cell count ( P = 0.0001) on admission (Figure 1). Patients with negative PCT had reduced antibiotic initiation (71% vs. 95%, P = 0.001) and were less likely to be admitted (89% vs. 98%, P = 0.078). A total of 460 PCT levels were collected [negative group: 303, median 2(2, 2), positive group: 157, median 4(3, 4)]. Patients with negative PCT had reduced antibiotic duration ( P < 0.001) and length of stay ( P = 0.004) (Figures 2 and 3). There were no reported adverse events or differences in 30-day pneumonia readmissions. Conclusion: Implementation of a PCT algorithm through ASP is a novel and efficacious addition to improving diagnostic yield, targeting appropriate therapy, and reducing length of stay. The impact on antibiotic resistance remains to be determined. Disclosures: All authors: No reported disclosures.